The Analysis of the Problems Solving Pattern on Wave Concept of the Physics Teachers’ Candidate - Sarwi, S; Nugroho, S E (Jurnal Pendidikan Fisika Indonesia, 2022)
The purpose of this research is to find the pattern of problem-solving of the wave concept. Qualitative research methods have been used. Think-aloud methods, essay tests, and interviews were used in data collection. Data analysis used qualitative analysis techniques. The results of the pattern of wave problem-solving by prospective teachers are formula-based methods, followed by P-prim and a small amount using analytical thinking. Difficulties in the effect of phase changes on the shape and value of displacement, and the propagation of string waves on the stationary wave of the Meld’s experiment. From the analysis, it is necessary to learn multi-representation of the concept of waves based on the type of problem-solving pattern was used. The benefits of research as input for monitoring the curriculum of the study program and increasing the interaction of wave physics learning.